Editorial of Special Issue "Body Image Perception and Body Composition in Different Populations: The Role of Physical Education and Sport" - Gianpiero Greco (MDPI AG, 2022)
Body image is the dynamic perception of one's body-how it looks, feels, and moves; it can change with mood, physical experience, and environment [...]